A Miscellaneous Hindrances to an Effective Response to Cable Theft in Durban Railway Stations, South Africa - Nobanda, Liso; Maweni, Vuyelwa Kemiso; Maluleke, Witness; Sibanyoni, Ephraim Kevin (International Journal of Criminology and Sociology, 2022)
This study focuses on notable miscellaneous hindrances to an effective response to cable theft in Durban railway stations of South Africa. From a qualitative standpoint; data was collected from Eight (8) purposively selected individuals to solicit their respective perceptions and experiences on this subject. This involved the Passenger Rail Agency of South Africa (PRASA) ‘Security Personnels – Cable Theft Investigators and Cable Theft Railway Patrollers, all involved in combating cable theft in Durban railway stations. Inductive Thematic Analysis was used for data analysis. This study found that scrap metal dealers are the major key contributors to cable theft in the Durban railway stations; and also the value of copper cable on the market promotes the exponential rise of cable theft. It was also established that, there was no proper protection of the rail infrastructure, and cable thieves get lighter sentences. It was further stablished that cable theft is perpetuated by the shortage of indispensable resources and workforce or police visibility in the stations. For the recommendations: More attention must be paid to scrap metal dealers by offering strict rules on the issuing of trading licenses. Moreover, severe stiff sentences should be handed to pontetial offenders and better working relations should be established, with more resources geared to the PRASA security department.